1985
DOI: 10.1128/aem.50.5.1149-1154.1985
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metals on Legionella pneumophila growth in drinking water plumbing systems

Abstract: An investigation of the chemical environment and growth of Legionella pneumophila in plumbing systems was conducted to gain a better understanding of its ecology in this habitat. Water samples were collected from hospital and institutional hot-water tanks known to have supported L. pneumophila and were analyzed for 23 chemical parameters. The chemical environment of these tanks was found to vary extensively, with the concentrations of certain metals reaching relatively high levels due to corrosion. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
5

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 38 publications
2
31
0
5
Order By: Relevance
“…Additionally, among the four metals examined, only iron concentration significantly correlated with Legionella contamination. This promotive activity of iron agrees well with the findings of States et al. (1985), who showed that a high concentration of iron (>1·0 mg l −1 ) in hot water tanks enhanced Legionella growth 2‐ to 100‐fold.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, among the four metals examined, only iron concentration significantly correlated with Legionella contamination. This promotive activity of iron agrees well with the findings of States et al. (1985), who showed that a high concentration of iron (>1·0 mg l −1 ) in hot water tanks enhanced Legionella growth 2‐ to 100‐fold.…”
Section: Discussionsupporting
confidence: 91%
“…The concentration of metals in hot-water tanks was shown previously to influence the multiplication of L. pneumophila. Low concentrations of iron and zinc, for example, enhanced the growth of L. pneumophila inoculated into hot-water tank samples and in tap water supplemented with other metals (28). The high levels of sulfide and/or the high pH at sites 1F and 1H may have contributed to the inhibition of growth or survival of Legionella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Iron limitation leads to greatly reduced virulence of Legionella (James et al, 1995). Metal plumbing components and associated corrosion products are important factors in providing iron and other metals that support the survival and growth of L. pneumophila in plumbing systems and may also be important in related habitats, such as cooling towers and air-conditioning systems (States et al, 1985).…”
Section: Environmental Sources Of Legionellosismentioning
confidence: 99%